Behavioral Pure-Tone Threshold Shifts Caused by Tympanic Membrane Electrodes. Issue 4 (July 2016) - Smith, Spencer B.; Lichtenhan, Jeffery; Cone, Barbara
Abstract : Objective: To determine whether tympanic membrane (TM) electrodes induce behavioral pure-tone threshold shifts. Design: Pure-tone thresholds (250 to 8000 Hz) were measured twice in test (n = 18) and control (n = 10) groups. TM electrodes were placed between first and second threshold measurements in the test group, whereas the control group did not receive electrodes. Pure-tone threshold shifts were compared between groups. The effect of TM electrode contact location on threshold shifts was evaluated in the test group. Results: TM electrodes significantly increased average low-frequency thresholds, 7.5 dB at 250 Hz and 4.2 dB at 500 Hz, and shifts were as large as 25 dB in individual ears. Also, threshold shifts did not appear to vary at any frequency with TM electrode contact location. Conclusions: Low-frequency threshold shifts occur when using TM electrodes and insert earphones. These findings are relevant to interpreting electrocochleographic responses to low-frequency stimuli. Abstract : Electrocochleography measurements are commonly made with electrodes that directly contact the tympanic membrane and are held in place with a foam insert earphone. This study investigated the effects of placing tympanic membrane electrodes on behavioral pure tone thresholds. Results indicate that tympanic membrane electrodes cause low-frequency threshold shifts as large as 25 dB, regardless of electrode contact location on the tympanic membrane. These findings should be considered when using low-frequency stimuli, such as chirps, tone bursts, or steady-state tones, to evoke electrocochleographic responses.